Intraoperative three-dimensional navigation for surgical treatment of osteoid osteoma in the foot and ankle – A series of 14 cases. Issue 8 (December 2022) - Gurel, Ron; Amzallag, Nisan; Benady, Amit; Efrima, Ben; Barriga, Juan; Gortzak, Yair; Sternheim, Amir; Dadia, Solomon; Hasbani, Nathan; Segal, Ortal
Abstract: Background: The surgical treatment for osteoid osteoma (OO) in the foot and ankle is challenging. It is difficult to locate the lesion and the anatomy is crowded by sensitive structures. The purpose of this study was to describe the outcomes of navigated mini open-intralesional curettage (NMIC) or navigated minimally invasive radiofrequency ablation (NMRFA) in treating these lesions. Methods: All patients who underwent surgery for OO in the foot and ankle between 2015 and 2020 were included. O-arm navigation was used in All procedures. The choice of NMIC versus NMRFA was made by the surgeon according to the location of the lesion and its proximity to sensitive anatomic structures. Results: Fourteen patients were included. Ten were operated by NMRFA and 4 by NMIC. All patients' symptoms related to OO resolved following a single procedure. Average AOFAS score increased by 18.7 (P < .001). Three patients had the following complications: pathologic fracture, superficial infection and transient deep peroneal nerve sensory loss. Conclusion: Navigated surgical treatment of OO in the foot and ankle is accurate, efficient and safe.